Relationship between deformation structure and petroleum accumulation and preservation, Qiangtang Basin, Tibet - Zu-jun GUO; Yong-tie LI; Zheng-bing NAN; He-fei YE (Petroleum Exploration and Development, 2008)
There are about 235 outcropped anticlines in Qiangtang Basin, Tibet that are dominantly of Jurassic age. Based on geophysical exploration, surface geologic survey, and regional tectonic stress, these anticlines can be classified into four types, that is, simple structure, united structure, complex structure, and twisted structure. These four types of structures are distributed in different places in the basin and are mainly formed in the two deformation phases during the late Yanshan movement and Himalayan movement. As the two phases match with the two periods of hydrocarbon generation, the structures provide good conditions for hydrocarbon accumulation. The new tectonic movement of Qinghai-Tibet plateau is generally thought to be the important factor causing reservoir damage. However, the analysis of fault nature, effective seal rock distribution, and plateau uplifting indicates that the faults in the basin are mainly compressive, the internal structure is stable, and the intervals of interest are well preserved and have a good exploratory potential. Key words: deformation structure, petroleum accumulation, preservation condition, Qiangtang Basin